Dopamine D1 and D2 receptors differentially control strength and dynamics of abstract decision codes in the primate prefrontal cortex - Esther F. Kutter; Pooja Viswanathan; Andreas Nieder (Proceedings of the National Academy of Sciences, 2026)
Dopamine critically modulates prefrontal circuits underlying cognitive control, but how D1-type (D1R) and D2-type (D2R) receptors influence abstract decision coding is unclear. We recorded single-neuron activity in two monkeys performing a number comparison task, in which abstract decisions about sequentially presented dot displays were dissociated from motor responses, while locally stimulating D1R or D2R via microiontophoresis. D1R stimulation suppressed, whereas D2R stimulation enhanced, the decision-coding strength of individual neurons, effects mirrored at the population level in decoding accuracy. Interestingly, dopamine receptors also bidirectionally modulated the temporal structure of population activity: D1R stimulation reduced the temporal generalizability of neuronal decision selectivity, suggesting more transient tuning and a shift toward a more dynamic coding regime. Conversely, D2R stimulation increased temporal generalizability of decision selectivity, implying more sustained tuning and a shift toward a more static coding regime. These findings suggest that D1- and D2-mediated mechanisms in the prefrontal cortex provide a receptor-specific substrate for balancing cognitive flexibility and stability in abstract decision-making. This pattern may reflect task-dependent deviations from classical dual-state models, in which D1 receptor activity stabilizes working memory representations whereas D2 receptor activity supports flexible coding—a relationship that appears reversed in the context of abstract decision formation.